2015
DOI: 10.1038/nm.3947
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BAP1 function leads to EZH2-dependent transformation

Abstract: Introductory Paragraph BAP1 and ASXL1 interact to form a polycomb deubiquitinase complex that removes monoubiquitin from histone H2A lysine 119 (H2AK119Ub). However, BAP1 and ASXL1 are mutated in distinct cancer types, consistent with independent roles in regulating epigenetic state and malignant transformation. Here we demonstrate that Bap1 loss results in increased trimethylated histone H3 lysine 27 (H3K27me3), elevated Ezh2 expression, and enhanced repression of Polycomb Repressive Complex 2 (PRC2) targets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
262
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(280 citation statements)
references
References 39 publications
11
262
6
1
Order By: Relevance
“…While these clinical studies demonstrate lack of benefit after pharmacologic inhibition of histone deacetylase to target epigenetic regulation in MPM, a preclinical study identified synthetic lethality with pharmacologic inhibition of enhancer of zeste 2 polycomb repressive complex 2 subunit (Ezh2) in MPM cells lacking Bap1 (124). A phase II study evaluating efficacy of the EZH2 inhibitor tazemetostat in patients with both Bap1-deficient and wild-type relapsed or refractory MPM is currently ongoing (clinicaltrials.gov NCT02860286).…”
Section: Targeting Epigenetic Regulatorsmentioning
confidence: 99%
“…While these clinical studies demonstrate lack of benefit after pharmacologic inhibition of histone deacetylase to target epigenetic regulation in MPM, a preclinical study identified synthetic lethality with pharmacologic inhibition of enhancer of zeste 2 polycomb repressive complex 2 subunit (Ezh2) in MPM cells lacking Bap1 (124). A phase II study evaluating efficacy of the EZH2 inhibitor tazemetostat in patients with both Bap1-deficient and wild-type relapsed or refractory MPM is currently ongoing (clinicaltrials.gov NCT02860286).…”
Section: Targeting Epigenetic Regulatorsmentioning
confidence: 99%
“…Hematopoieticspecific conditional loss of Bap1 resulted in retention of monoubiquitinated H2AK119 and decreased expression levels of transcriptional regulator host cell factor-1 (HCF1) and OGT, leading to MDS/MPN-like disease in vivo [98]. However, in contrast to Asxl1 loss, Bap1 deletion was shown to increase Ezh2 and H3K27me3 levels and enhance repression of PRC2 targets, sensitizing BAP1-deficient mesothelioma to pharmacologic EZH2 inhibition [99]. These data indicate that ASXL1 and BAP1 loss may function in independent manner in myeloid transformation.…”
Section: Asxl1mentioning
confidence: 99%
“…BAP1 mutations decreased occupancy of BAP1 as well as L3MBTL2 within the EZH2 promoter. Relative to MPM cells expressing BAP1, MPM cells with BAP1 mutations were markedly more sensitive to pharmacologic inhibitors of EZH2 in-vitro and in-vivo (92), suggesting that BAP1 mutations render MPM cells addicted to PRC-2.…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 99%
“…Conceivably, global and promoter-specific PRC-2 marks, DNA methylation, micro-RNA and gene expression profiles, as well as responses to biochemical or pharmacologic inhibition of PRC-2 activity may be contingent on BAP1 mutation status as well as magnitude of EZH2 over-expression in MPM. In a series of elegant experiments, LaFave et al (92) observed that BAP1 mutations, which typically result in loss of protein expression, increased EZH2 as well as SUZ12 expression in MPM cells. Up-regulation of EZH2 in BAP1 mutant cells was associated with reduced levels of H4K2Me1, as well as decreased occupancy of L3MBTL2 (an atypical polycomb protein which recognizes this repressive histone mark) within the EZH2 promoter (96,97).…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation